Kesiapan Rumah Sakit Umum Daerah Undata Palu Dalam Penanganan Korban Bencana - Ismundandar, (Jurusan Keperawatan FIKES UNSOED, 2013)
The research was conducted in Undata Regional General Hospital Palu. This was a qualitative design research with the phenomenological approach. The research results indicates that the hospital disaster management team has been established, the human resources readiness has been sufficient, the facilities of the disaster victims handling are still lack, Standard Operating Procedure (SOP) of the disaster management is still lack, there is no specific budget for disaster victim handling. Disaster Management Team has been in active for long time. They do not have the primary facilities/infra-structure needed in the disaster handling. They do not have SOP of work health and safety, guidelines of emergency management, disaster management procedure and the budget usedindisaster management is an extra fund (operating fund).